Knowledge, attitude, and awareness of childhood cancer among undergraduate medical students in South India - M Sneha Latha; Kumaravel Chitralakshmi; Manipriya Ravindran; P Ravichandran Angeline; Lakshminarayanan Kannan; Julius Xavier Scott (South Asian Journal of Cancer, 2015)
Background :In India roughly 60000 childhood cancer cases are diagnosed annually with only nearly 100 pediatric oncologists. So it′s pertinent that the physicians and pediatricians are adequately equipped to recognize and refer them appropriately. Hence this study was conducted to assess the knowledge, attitude and awareness of childhood cancer among undergraduate medical students in South India. Materials and Methods: The study was conducted among 240 undergraduate students from all over South India in a undergraduate pediatric clinical training. A 24 point questionnaire was given to assess their understanding of pediatric malignancies and their interest towards pediatric oncology. Statistical analysis was done with SPSS 18.V software. Results: 50% were interested in pursuing pediatrics as their career but 80% of them were not interested in pursuing pediatric oncology as their career. 55% of the students have not encountered any pediatric oncology patients in the ward. 40% did not have any lecture classes on pediatric oncology. 65.5% felt that their knowledge of childhood cancer did not make them competent to suspect and refer appropriately during their practice. 84% supported that there is a need to improve pediatric oncology teaching in their medical curriculum. Conclusions : The study unambiguously states that the future physicians lack confidence in identifying and managing childhood malignancies and pediatric oncology is far down in their career options. There is a need to reform the undergraduate medical students by increasing their exposure to pediatric oncology to improve their competence levels and interest in pursuing it as a career also.